A Strategy for Improving Dynamic Composability: Ontology-driven Introspective Agent Architectures - Levent Yilmaz (Journal of Systemics, Cybernetics and Informatics, 2007)

(untitled)
Seamless composability of disparate simulations within a systems of systems context is challenging. Large complex simulations must respond to changing technology, environments, and objectives. The problem exacerbates when dynamic extensibility and adaptability are significant concerns in an application domain. Simulations that are dynamically extensible, while being composable require principled designs that facilitate engineering interoperability and composability in the first place. The role of ontologies and their axiomatization is discussed as a potential strategy to improve dynamic composability.